The Airplane Boneyard Studio: Considering Stillness and Creative Practice from an Airplane Wing - Castleden, Susanna (Taylor and Francis, 2018)
In 1975, Australian artist Ian Howard taped sheets of paper to the nose of the Enola Gay, and through rubbing the surface with a thin layer of wax crayon, he created a ghost-like impression of the airplane that dropped an atomic bomb on Hiroshima. Forty years later, in an aircraft boneyard in Arizona, I placed redundant maps of the Great Sandy Desert on the wing of a passenger jet to take an imprint of a similarly disused yet functionally different aircraft. Despite the conceptual and temporal differences that separated these two acts, the process of rubbing—or frottage—resulted in two artworks that revealed traces of the physical encounter with the aircraft surfaces, the dynamic handling of the materials of making, and the practical and aesthetic impact of working in the field. By its very nature of proximity and touch, the process of frottage records a bodily engagement with both object and environment. Recounting the experiences of working on the wing of a civilian plane in the desert heat of Arizona forty years after Howard worked on the Enola Gay, I reflect on the low-tech process of frottage and its capacity to suggest our respective embodied experiences of making. Furthermore, I suggest that traces of environmental factors such as high humidity, desert winds, or extreme heat, or time-based factors such as limited access to stationary airplanes can be captured and archived through creative practice as a way to contribute to contemporary understandings of mobility and its counterpart stillness.